Ameliorating Spinal Cord Injury in an Animal Model With Mechanical Tissue Resuscitation. Issue 6 (June 2016) - Zheng, Zhen-lin; Morykwas, Michael J.; Tatter, Stephen; Gordon, Stan; McGee, Maria; Green, Heather; Argenta, Louis C.
Abstract : BACKGROUND: Traumatic spinal cord injury (SCI) is a major worldwide cause of mortality and disability with limited treatment options. Previous research applying controlled negative pressure to traumatic brain injury in rat and swine models resulted in smaller injuries and more rapid recovery. OBJECTIVE: To examine the effects of the application of a controlled vacuum (mechanical tissue resuscitation [MTR]) to SCI in a rat model under several magnitudes of vacuum. METHODS: Controlled contusion SCIs were created in rats. Vacuums of −50 and −75 mm Hg were compared. Analysis included open-field locomotor performance, magnetic resonance imaging (in vivo T2, ex vivo diffusion tensor imaging and fiber tractography), and histological assessments. RESULTS: MTR treatment significantly improved the locomotor recovery from a Basso, Beattie, and Bresnahan score of 7.8 ± 1.9 to 11.4 ± 1.2 and 10.7 ± 1.9 at −50- and −75-mm Hg pressures, respectively, 4 weeks after injury. Both pressures also reduced fluid accumulations > 10% by T2-imaging in SCI sites. The mean fiber number and mean fiber length were greater across injured sites after MTR treatment, especially with treatment with −50 mm Hg. Myelin volume was increased significantly by 60% in the group treated with −50 mm Hg. CONCLUSION: MTR of SCI in a rat model is effective in reducing edema in the injured cord, preserving myelin survival, and improving the rate and quantity of functional recovery. ABBREVIATIONS: BBB, Basso, Beattie, and Bresnahan DTI, diffusion tensor imaging FA, fractional anisotropy MTR, mechanical tissue resuscitation MTR50, mechanical tissue resuscitation with 50-mm Hg subatmospheric pressure MTR75, mechanical tissue resuscitation with 75-mm Hg subatmospheric pressure ROI, region of interest SCI, spinal cord injury